The Global Influence of the Seventh-Day Adventist Church on Diet - Banta, Jim E. (Religions, 2018)
The emphasis on health ministry within the Seventh-day Adventist (SDA) movement led to the development of sanitariums in mid-nineteenth century America. These facilities, the most notable being in Battle Creek, Michigan, initiated the development of vegetarian foods, such as breakfast cereals and analogue meats. The SDA Church still operates a handful of food production facilities around the world. The first Battle Creek Sanitarium dietitian was co-founder of the American Dietetics Association which ultimately advocated a vegetarian diet. The SDA Church established hundreds of hospitals, colleges, and secondary schools and tens of thousands of churches around the world, all promoting a vegetarian diet. As part of the health message,' diet continues to be an important aspect of the church's evangelistic efforts. In addition to promoting a vegetarian diet and abstinence from alcohol, the SDA church has also invested resources in demonstrating the health benefits of these practices through research. Much of that research has been conducted at Loma Linda University in southern California, where there have been three prospective cohort studies conducted over 50 years. The present study, Adventist Health Study-2, enrolled 96,194 Adventists throughout North America in 2003-2004 with funding from the National Institutes of Health. Adventist Health Studies have demonstrated that a vegetarian diet is associated with longer life and better health.